The Effectiveness of the Outdoor Study Method in Improving Students’ Ecological Intelligence in Geography Learning at SMAN 6 Muaro Jambi - Nur Sya'bani S; Yurni Suasti; Dedi Hermon; Bayu Wijayanto (Postgraduate, University of Mataram, 2025)
This study aimed to examine the effectiveness of the outdoor study method in improving students’ ecological intelligence in geography learning at SMAN 6 Muaro Jambi. A quantitative approach with a quasi-experimental non-equivalent control group design was employed, involving 60 eleventh-grade students, divided equally into an experimental group receiving outdoor study instruction and a control group receiving conventional classroom learning. Ecological intelligence was measured using a validated five-point Likert-scale questionnaire administered as both the pretest and posttest, which served as the sole quantitative data source. Observation sheets were used only as supporting documentation of learning activities. Data analysis included descriptive statistics, normality and homogeneity tests, and Analysis of Covariance (ANCOVA) to control initial differences in pretest scores. The ANCOVA results indicated that the pretest covariate significantly influenced posttest scores, and after controlling for this effect, the outdoor study method produced a statistically significant increase in ecological intelligence (p < 0.001). Students in the experimental group achieved higher adjusted mean scores compared with the control group. The findings demonstrate that outdoor study is an effective experiential learning approach that meaningfully enhances ecological awareness, sensitivity, and environmentally responsible tendencies in secondary school geography education.